Functional Outcome of Total Knee Replacement in Patients with Rheumatoid Arthritis (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To evaluate the functional outcome of Rheumatoid Arthritis (RA) undergoing primary total knee arthroplasty (TKA). Methods: Data was analyzed from Pakistan National Joint Registry (PNJR) from April 2014 to April 2015 to assess functional outcome of all patients who underwent TKA by a single surgeon and had a diagnosis of rheumatoid arthritis using Knee Society Scores (KSS) preoperatively and postoperatively at 3 months, 6 month and 1 year. Results: Out of 39 patients 31 were female and 8 were male with mean age of 55.58Â±8.35 and mean Body Mass Index of 29.21Â±4.80.Within 39 patients, 22 patients had left sided TKA and 17 patients had right sided TKA. The mean average of Knee and Function score was 95.38Â±1.23 and 94.17Â±9.87 respectively after 1 year follow up. Average knee range of motion had increased from 98.52Â±2.46 degrees preoperatively to 109.37Â±3.61 degrees postoperatively. Conclusion: Total knee arthoplasty in patients with rheumatoid arthritis is a good surgical option with about 71.8 percent of people having excellent functional outcome according to knee society scoring system.